Lichen planus: a comprehensive evidence‐based analysis of medical treatment. (22nd July 2019) - Husein‐ElAhmed, H.; Gieler, U.; Steinhoff, M.
Abstract: Lichen planus (LP) is a chronic‐relapsing inflammatory skin disease. Although many drugs have been used for the management of LP, some of them lack the backup by strong therapeutic evidence, while others are not suitable for some patients due to safety profile issues. The aim of this study was to review the recent status of available medical therapies for LP to help physicians make better decisions upon best medical practice while facing patients with this condition. A review of published articles on management of LP was conducted with the MEDLINE and PubMed databases. The quality of the evidence was graded as high, moderate, low or very low. A total of 1366 articles were retrieved, and 219 (16%) were included in the final analysis. Twenty‐one different treatment modalities were analysed. The quality of evidence was high for topical steroid and calcineurin inhibitor, while it was moderate for oral steroids. All the other modalities reached low or very low quality of evidence. Topical steroids and calcineurin inhibitors are the current first‐line therapies, while for other therapies the strength of recommendation is not so evident. Unfortunately, larger randomized, controlled trials to support the efficacy, safety and tolerability of other therapies in LP are lacking, and many of them are recommended based on studies with small sample sizes, lack of standardized outcome measures or lack of controlled duration or even in anecdotal evidence. Thus, large‐scale randomized clinical trials are still warranted to establish the exact benefits of other topical treatments, phototherapy, immunosuppressant and new immunomodulators for an optimized treatment of LP.